Low Genetic Diversity of the Only Clade of the Tick Rhipicephalus microplus in the Neotropics - Díaz-Sánchez, Sandra; Hernández-Triana, Luis M.; Labruna, Marcelo B.; Merino, Octavio; Mosqueda, Juan; Nava, Santiago; Szabó, Matías P.J.; Tarragona, Evelina Luisa; Venzal, José Manuel; de La Fuente, José; Estrada-Peña, Agustín (MDPI, 2024)
This study addresses the variability of the mitochondrial cytochrome oxidase subunit I (COI) and 16S rDNA (16S), and nuclear internal transcriber spacer ITS2 (ITS2) genes in a set of field-collected samples of the cattle tick, Rhipicephalus microplus (Canestrini, 1888), and in geo-referenced sequences obtained from GenBank. Since the tick is currently considered to be a complex of cryptic taxa in several regions of the world, the main aims of the study are (i) to provide evidence of the clades of the tick present in the Neotropics, (ii) to explore if there is an effect of climate traits on the divergence rates of the target genes, and (iii) to check for a relationship between geographical and genetic distance among populations (the closest, the most similar, meaning for slow spread). We included published sequences of Rhipicephalus annulatus (Nearctic, Afrotropical, and Mediterranean) and R. microplus (Afrotropical, Indomalayan) to fully characterize the Neotropical populations (total: 74 16S, 44 COI, and 49 ITS2 sequences included in the analysis). Only the clade A of R. microplus spread in the Nearctic–Neotropics. Both the K and Lambda’s statistics, two measures of phylogenetic signal, support low divergence rates of the tested genes in populations of R. microplus in the Neotropics. These tests demonstrate that genetic diversity of the continental populations does not correlate either with the geographic distance among samples or with environmental variables. The low variability of these genes may be due to a combination of factors like (i) the recent introduction of the tick in the Neotropics, (ii) a large, effective, and fast exchange of populations, and (iii) a low effect of climate on the evolution rates of the target genes. These results have implications for the ecological studies and control of cattle tick infestations.